Save-a-tooth: Conservative surgical management of dentigerous cyst - Shivaprakash P; Rizwanulla T; Baweja D; Noorani H (Wolters Kluwer Medknow Publications, 2009)
Dentigerous cysts are the most common bony lesions of the jaws in children. It is one of the most prevalent types of odontogenic cysts associated with an erupted or developing tooth, particularly the mandibular third molars; the other teeth that are commonly affected are, in order of frequency, the maxillary canines, the maxillary third molars, and rarely the central incisors. Radiographically, the cyst appears as ovoid well-demarcated unilocular radiolucency with a sclerotic border. Careful evaluation of the history and the clinical and radiographical findings help clinicians to currently diagnose the condition, identify the etiological factors, and administer the appropriate treatment.